PANIC BUYING: ITS CORRELATION WITH THE PRACTICE OF IKHTIKAR AND QS. HUD VERSE 61 REGARDING THE COMMAND TO PROSPER THE EARTH - Hasan, Irmayanti; Amalia, Husna; Huwaidi, M. Hibatullah; Amani, Fitriyatul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 10 No 1 (2024): The 10th International Conference of Islamic Economics and Business (ICONIES 2024), 2024)
Panic buying behavior is a human behavior to consume impulsively in large quantities. This action is often based on the precautionary principle in terms of minimizing risk. This study aims to determine the correlation of panic buying with the practice of ikhtikar or hoarding in Islam and its relation to QS. Hud verse 61 which contains God's mandate to humans to always prosper the earth. This research was conducted using a qualitative method based on literature studies. The results of this study are that although it is based on precautionary principles, action panic buying is still prohibited because it can potentially harm the global economy. Besides that panic buying also give rise to ikhtikar or hoarding behavior which is strongly opposed in the implementation of sharia economics. There is action panic buying and also the effort is also very contrary to God's trust to man through His words in QS Hud: 61, to always maintain and prosper life on earth